DEEP-FAKES AND FRACTURED REALITIES: RECONFIGURING TRUST IN DIGITAL MEDIA - Hashmi, Rashid; Shukla, Rajesh Kumar; Sharma, Ramesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The paper is a critical analysis of the way artificial intelligence-generated deep-fakes undermine authenticity in media, journalistic credibility, platform regulation, and democratic discourse. It identifies gap in current literature that missing a comprehensive theoretical framework, which would describe the systemic and multi-layered erosion of trust created by synthetic media. To address this gap, the article introduces Fractured Reality Framework that is a novel synthesis of media ecology, post-truth theory, platform capitalism, algorithmic governance, and critical AI ethics. The conceptual framework represents the mediated reality as a stratified system of authentic, synthetic, hybrid, and fractured layers, recursively punctured by algorithmically amplified feedback loops. The analysis places deep-fakes as the ecological powers that multiply the level of epistemological uncertainty, social inequalities, and political manipulation with far-reaching consequences to the working of the democratic communication and the media system.